The Triple Nexus: Personality Traits, Cognitive Function, and Quality of Life in Alcohol-Dependent Youth - Ms. Rosy Arora,; Dr. Kiran Srivastava, (The Bioscan, 2025)
Alcohol dependence in youth is an essential area of public health concern with an enormous impact on mental health and development, as well as on quality of life (QoL). This research offers an integrative analysis of personality traits, cognitive abilities, and QoL in alcohol-dependent youth based on demographic characteristics of family status, marital status, education, and occupation. In the present study, data were collected from fifty participants across de-addiction clinics in semi-urban Punjab in a cross-sectional manner with purposive sampling. Descriptive analysis and inferential methods, including analysis of variance (ANOVA) and t-tests, were used for data analysis. Youth from nuclear families had better QoL and cognitive abilities, while youth from joint families had more vital personality traits. Marital status revealed contrasting patterns: married participants had higher scores on personality tests than unmarried participants who performed better on cognitive tests. The level of education was also significant, and the participants with middle school education had the highest QoL and cognitive scores, while those with high education had better personalities. There was considerable variation by occupational status; youth in private employment had the best QoL and cognitive performance, while drivers had the worst outcomes but higher levels of personality resilience. The findings from the sequence reinforce the need for assessment of the various aspects of alcohol dependence, especially in the context of the demographic environment of youths who are affected. The interplay between personality traits, cognitive impairments, and QoL highlights the complexity of addressing alcohol-related issues. By addressing existing gaps, this study contributes to a deeper understanding of alcohol dependence and its far-reaching impact on youth development.